2021
DOI: 10.2196/32951
|View full text |Cite
|
Sign up to set email alerts
|

Digitization and Health in Germany: Cross-sectional Nationwide Survey

Abstract: Background Digital technologies are shaping medicine and public health. Objective The aim of this study was to investigate the attitudes toward and the use of digital technologies for health-related purposes using a nationwide survey. Methods We performed a cross-sectional study using a panel sample of internet users selected from the general population living in Germany. Responses to a survey with 28 items … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 31 publications
1
27
0
3
Order By: Relevance
“…The contribution of these elements to the success or failure of digital interventions for physical activity promotion is unclear, primarily because this information was either not coded in reviews or not reported in the primary studies. Furthermore, sociodemographic factors, including age, gender, education, income, and digital health literacy, affect the use of and interest in digital health technologies [ 1 ] and could also facilitate or hinder the efficacy of digital interventions. Further research is needed to identify health needs or barriers associated with digital health technology use in low socioeconomic settings [ 65 ] to improve the efficacy of digital interventions for physical activity promotion in such populations [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contribution of these elements to the success or failure of digital interventions for physical activity promotion is unclear, primarily because this information was either not coded in reviews or not reported in the primary studies. Furthermore, sociodemographic factors, including age, gender, education, income, and digital health literacy, affect the use of and interest in digital health technologies [ 1 ] and could also facilitate or hinder the efficacy of digital interventions. Further research is needed to identify health needs or barriers associated with digital health technology use in low socioeconomic settings [ 65 ] to improve the efficacy of digital interventions for physical activity promotion in such populations [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the reviews included in this scoping review predominantly focused on mixed healthy or clinical samples and predominantly adult populations. Since digital interventions can support health promotion and disease prevention [ 1 ], future research should focus on the evaluation of digital interventions or digital tools in healthy populations to promote healthy lifestyle, including physical activity. Furthermore, children and adolescents are important target populations for digital interventions that focus on physical activity promotion because the use of digital technologies contributes to sedentary behavior, especially in early childhood [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not use validated instruments or methods for user technology acceptance in this work, such as the unified theory of acceptance and use of technology model, as our focus was not on a thorough technology acceptance investigation but rather on obtaining a general status quo of use, attitudes, and behavior of surgical patients in terms of new digital health technologies. However, recently, much work has been done regarding digitization and digital health technology in Germany, which we will use to design future trials [ 49 - 51 ]. For further studies, it would be recommended to use additional validated instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The field of digital public health is rapidly developing [1]. Digitization is likely to have a major impact on therapy in the future, and it already increasingly contributes to prevention and health promotion [2]. Interventions supported by modern technologies (ie, digital interventions [DIs]) are enormously popular in the context of healthy lifestyle and behavior change, including physical activity (PA) promotion [3,4].…”
Section: Introductionmentioning
confidence: 99%